Expression of Endocan in Tissue Samples from Prostate Adenocarcinoma and Prostate Hyperplasia: A comparative retrospective study - Dadali, Mumtaz; Tad, Murat; Bagbanci, Muhammed Sahin (Urology Journal, 2021)
Purpose: In this study, we aimed to determine whether there is a significant difference in endocan expression levels between prostate adenocarcinoma and prostate hyperplasia tissues by using an immunohistochemical method. Materials and Methods: All of 51 patients, who were getting treatment for the last 5 years, participated in the study. 31 of 51 patients underwent transrectal sonography (TRUSG) -assisted prostate biopsy because of prostate adenocarcinoma as diagnosed with elevated PSA levels and histopathological examination. The remaining 20 patients comprised the control group. The control group included patients with benign prostate hyperplasia based on pathological examination. Results: It was found that there was strong positive epithelial staining in 74.2% of patients with prostate cancer while in 5% of controls, indicating a statistically significant difference (P < .001). It was also found that the rate of strong positive endothelial staining was 77.4% in the patient group whereas 5% in the control group (P < .001). Also, the rate of strong positive stromal staining was 64.5% in the patient group while 5% in the control group (P < .001). Conclusion: We found that tissue endocan expression level was statistically significantly higher in patients with prostate cancer compared to those with benign prostate hyperplasia by using an immunohistochemical method.